Optimasi Visualisasi Celah Sendi Glenohumeral pada Kasus Trauma Bahu melalui Proyeksi Axillary View dengan Sudut 25° Caudal - Wulandari, Andi Nur Intan; Ibrahim, Irsyadah; Darmawan, Zulkifli Tri; Syuhada, Firdha Adlia; Arung, Panji (Poltekkes Kemenkes Semarang, 2026)
Background: The shoulder joint is a complex anatomical structure with an extensive range of motion, making it highly susceptible to traumatic injuries such as fractures and dislocations. Conventional radiography often faces limitations in providing detailed visualization of these injuries, necessitating specialized projection techniques to clarify anatomical abnormalities. This study aims to evaluate the implementation of the axillary view projection using a 25° caudal angle in trauma cases at RSKB Columbia Asia Pulomas Jakarta. Methods: This study utilized a qualitative descriptive approach with a case study design at the Radiology Department of RSKB Columbia Asia Pulomas Jakarta from January to March 2025. One patient requiring shoulder joint examinations served as the primary subjects. Data were collected through direct observation of the radiographic procedures, interviews with radiographers and radiologists, and analysis of clinical documentation. Results: The examination technique involved positioning the patient seated beside the table with the arm abducted over the image receptor. The central ray was directed at the glenohumeral joint using a 25° caudal angulation. The findings indicate that the 25° caudal angle is particularly beneficial for non-cooperative patients, as it successfully opens the glenohumeral joint space and visualizes the axillary region clearly. This technique effectively revealed clinical conditions, including subluxation, glenoid avulsion, and joint space narrowing. Conclusions: The axillary view with a 25° caudal angle is a reliable and effective technique for assessing shoulder trauma. It provides superior anatomical detail regarding the relationship between the humeral head and the glenoid fossa, thereby supporting more accurate clinical decision-making in trauma management.